The relationship between neck pain and cervical alignment in patients with temporomandibular disorders - Coskun Benlidayi, MD, Ilke; Guzel, MD, Rengin; Tatli, PhD, Ufuk; Salimov, PhD, Fariz; Keceli, PhD, Onur (Cranio, 2020)
: To elucidate the impact of neck pain on cervical alignment in patients with TMDs. : Patients diagnosed with TMDs between November 2013 and November 2015 were included. All subjects underwent lateral cervical X-ray evaluation and completed the RDC/TMD Axis II Biobehavioral Questionnaire for TMDs. Patients with neck pain also completed the Neck Pain & Disability Scale (NPDS). Cervical lordosis angle was measured according to C2-C7 Cobb's method. : The mean cervical lordosis angle of the whole group ( = 60) revealed hypolordosis (10.9 ± 12.7 . Cervical lordosis angle did not differ between patients with ( = 28) and without ( = 32) neck pain (12.2 ± 12.8 versus 9.8 ± 12.7 , respectively; = 0.46). TMD-related variables were not correlated with cervical alignment but were moderately correlated with NPDS score, with the exception of TMD-associated disability. : Patients with TMDs have hypolordotic cervical malalignment (tendency toward kyphosis) regardless of neck pain.